2011
DOI: 10.1186/1476-069x-10-50
|View full text |Cite
|
Sign up to set email alerts
|

Oral ingestion of hexavalent chromium through drinking water and cancer mortality in an industrial area of Greece - An ecological study

Abstract: BackgroundHexavalent chromium is a known carcinogen when inhaled, but its carcinogenic potential when orally ingested remains controversial. Water contaminated with hexavalent chromium is a worldwide problem, making this a question of significant public health importance.MethodsWe conducted an ecological mortality study within the Oinofita region of Greece, where water has been contaminated with hexavalent chromium. We calculated gender, age, and period standardized mortality ratios (SMRs) for all deaths, canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
103
2
13

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 216 publications
(120 citation statements)
references
References 13 publications
2
103
2
13
Order By: Relevance
“…In addition, our results regarding increased mortality from all cancers and specific cancer sites including lip, oral cavity and pharynx, liver, stomach, pancreas, prostate, colon and kidney and other genitourinary organs among females are in consistence with relevant epidemiological and animal studies, which indicated carcinogenesis after long-term consumption of drinking water contaminated with Cr(VI) (Beaumont et al, 2008;Linos et al, 2011;NTP, 2008). Similar to our outcomes, Linos et al (2011) showed that citizens residing in the industrial area of Oinofita were more likely to have higher mortality rates from primary liver (SMR = 1104.2, 95% CI 405.2-2403.3) and lung cancers (SMR = 145.1, 95% CI 100.5-202.8) in both males and females as well as kidney and other genitourinary organs among females (SMR = 367.8,3) compared to the population of the surrounding prefecture.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…In addition, our results regarding increased mortality from all cancers and specific cancer sites including lip, oral cavity and pharynx, liver, stomach, pancreas, prostate, colon and kidney and other genitourinary organs among females are in consistence with relevant epidemiological and animal studies, which indicated carcinogenesis after long-term consumption of drinking water contaminated with Cr(VI) (Beaumont et al, 2008;Linos et al, 2011;NTP, 2008). Similar to our outcomes, Linos et al (2011) showed that citizens residing in the industrial area of Oinofita were more likely to have higher mortality rates from primary liver (SMR = 1104.2, 95% CI 405.2-2403.3) and lung cancers (SMR = 145.1, 95% CI 100.5-202.8) in both males and females as well as kidney and other genitourinary organs among females (SMR = 367.8,3) compared to the population of the surrounding prefecture.…”
Section: Discussionmentioning
confidence: 82%
“…Yet, the California Environmental Protection Agency proposed the Public Health Goal of 0.02 μg of Cr(VI) per liter of drinking water (Office of Environmental Health Hazard Assessment [OEHHA], 2011). Such threshold was relied on the study of Linos et al (2011), which supported the hypothesis of Cr(VI) carcinogenicity via the oral ingestion pathway of exposure.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations